Molecularly imprinted electrochemical sensor based on electropolymerized glycine under reduced graphene oxide for determination of monorhamnolipids - de Souza, Matheus Bispo [UNESP]; de Araújo Souza, Barbara Camila [UNESP]; Stradiotto, Nelson Ramos [UNESP] (Elsevier, 2025)
In the present work, a molecularly imprinted electrochemical sensor containing polyglycine on poly-reduced graphene oxide (rGO) was developed to quantify monorhamnolipids (mono-RHL). Mono-RHL has a variety of applications, including use as a biosurfactant, bioremediation of pollutants, biodegradability of hydrocarbons, inhibition of biocidal activity, among others. The developed sensor is made of glassy carbon (GCE) and was coated with reduced graphene oxide (rGO), with electropolymerization of glycine (Gly). The parameters used in the molecular imprinting of the film were optimized, including the number of polymerization cycles, the concentration ratio [mono-RHL:Gly], the extraction time, the rebinding time and the rebinding pH. Electrochemical, microscopic and spectroscopic characterizations of the sensor were performed. The calibration curve was obtained in the concentration range 5.0 × 10−14–1.0 × 10−12 mol L−1, and the detection and quantification limits were calculated as 2.1 × 10−14 and 7.0 × 10−14 mol L−1, respectively, with a sensitivity of 217.5 μA/pmol L−1. The sensor is selective for mono-RHL and is evaluated with different interferents, having an impression factor (α) of 3.1. The sensor showed good repeatability, obtaining 7 different electrodes with a relative standard deviation (RSD) of 4.1 %. The sensor is also stable and can be reused up to 4 times, presenting a deviation of 7.5 % of the original current. The methodology was applied to a mono-RHL sample produced from Pseudomonas aeruginosa in a bioelectrochemical system, where a concentration of 10.9 × 10−6 mol L−1 was found. Recovery tests were performed obtaining values between 96.4 and 102.4 %.